Pembuatan Kompos Dari Sampah Organik Pasar dengan Menggunakan EM-4 - Erda Marniza; Sri Febriza (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
Waste disposal activity is an activity that is often done so that organic waste processing is needed. Organic waste has some difficulties in collection and disposal. Composting is a suitable process, because the raw material and the place and process do not depend on large tracts of land. Composting is a natural microbiological decomposition process from organic waste. One of the latest technologies in accelerating reactions is to use effective microorganisms (EM-4). Composting using EM-4 is a technology for activa ting microorganisms that already exist in a place, such as crop residues. This study aims to study the particle size and height of the pile of 5, 10, and 15 cm with the use of EM-4 to the value of the ratio C / N, P, K and pH. The results of the research that have been carried out show the process of making compost from market organic waste using an EM-4 activator. at the best process conditions obtained at particle size; garbage 3 cm, with a stack height of 10 cm with C / N, P, K and pH values ​​respectively 12.80%, 2.99%, 4.12% and 7.5. so the results obtained are still included in the SNI standard 19-7030-2004